Catástrofe e invación discursiva en Phaedra de Séneca - Vizzotti, Martín Miguel (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2006)
The tragedy's prologue unfolds two distinctive territories: Hippolytus' silvae and Phaedra's interior world of luxuries. Each character is defined by the environment that his or her speech configures: the chaste and wild woods of Hippolytus will reveal, under their sylvan austerity, a diction of violence and sterility which hints the inadecuation of the young hunter to the image of sapiens that part of the critic sees in him, while Phaedra's interior and overwhelming space will be crowded by flames and vapor, symbols of her passion. Both worlds stand as two separate environments: chill and flames, chastity and libido, snow and steam coexist unaware of each other, and in such condition neither tragedy nor catastrophe occur. They begin to unfold due to Phaedra's breaching of the boundary between them, The queen discursively steps into Hippolytus' siinae, progressively tainting them with the attributes of her world until they eventually turn into a locus horridus throught which the young hunter will flee in horror as the wild beasts he used to stalk. Therefore tragedy and catastrophe happens when Híppolytus' silvae are turned into a stalking nemus inhabited by luxurious creatures thanks to Phaedra's discursive invasion of the rough landscape configured by the character in his starting monody